A C-terminal peptide of TFPI-1 facilitates cytosolic delivery of nucleic acid cargo into mammalian cells - Fazil, Mobashar Hussain Urf Turabe (2021)
Efficient intracellular nucleic acid delivery into mammalian cells remains a long-standing challenge owing to poor cell permeability and uptake of naked nucleic acids across the cell membrane and limited cargo stability. Conventional delivery methods have several drawbacks, such as cytotoxicity, limited cell-type applicability, low efficiency, hindrances that limit the potential of oligonucleotide delivery in functional genomics, therapeutics and diverse research applications. Thus, new approaches that are robust, safe, effective and valid across multiple cell types are much needed. Here, we demonstrate that GGL27, a TFPI-1-derived novel cationic host defence peptide, facilitates the delivery of nucleic acid cargo into the cytosol of a range of mammalian cells. The GGL27 peptide is non-cytotoxic and is internalized in a broad range of mammalian cell-types, including transformed cell lines and primary cells. GGL27 spontaneously forms complexes with nucleic acids of variable sizes, protects them from nuclease degradation, and delivers cargo effectively. Together, our observations demonstrate the versatile cell-penetrating property of GGL27, providing an excellent template for developing a simple, non-toxic peptide-based cytosolic delivery tool for wide use in biomedical research.